(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
For learners, learning a new language can be a challenging process at times. However, there are a number of approaches to teaching foreign languages that enable educators to facilitate this process. This article discusses several interactive approaches to teaching language and the advantages they offer students.